Analisis Produktivitas Kerja Pegawai dari Kontribusi Faktor Komunikasi, Budaya Kerja, dan Motivasi Kerja (Studi di Kantor Camat Kuala Kabupaten Bireuen) - Alhalim, Alhalim; Luthfi, Luthfi; Humaira, Novida (Singkite Journal, 2025)
This case study analyzed employee work productivity through the influence of communication, work culture, and work motivation factors. The study involved 43 employees at the Kuala District Office in Bireuen Regency, using descriptive and verification methods with a quantitative research approach. Data collection techniques included observation and questionnaires, and analysis using a multiple regression model. The results showed: 1) There were direct and indirect positive contributions from communication factors on employee work productivity of 23.71%, work culture factors of 23.26%, and work motivation factors of 25.23%. 2) Simultaneously, communication, work culture, and work motivation contributed 57.0% to employee work productivity.